Preventive gynaecology: awareness, attitude and practices of gynecologists - Patne, Smita S.; Upadhye, Aditi J.; Shembekar, Shantanu C.; Shembekar, Chaitanya A.; Upadhye, Jayshree J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Gynecologists are aware of screening tests of all gynecological malignancies. However, attitude and practices do not match with this. Present study was conducted in 214 gynecologists to evaluate awareness, attitude and practices of preventive gynecology. Methods: A survey was conducted among 214 gynecologists of Nagpur, using a questionnaire. This evaluated implementation of screening and preventive measures used by them for self-protection as well as for the women seeking their services. Their attitude regarding HPV vaccine as a preventive measure was also noted. Results: In present study, 160 (74.76%) gynecologists routinely advice pap smear to the patients, 54 (25.23%) gynecologists advice pap smear to the patients only if it is indicated. 102 (47.66%) gynecologists and spouses have got their own pap smear done. 192 (89.71%) were doing their self breast examination regularly and 66 (30.84%) had done their mammography. 168 (78.50%) had their ultrasound done and 98 (45.79%) had their P/V done. 132 (61.68%) are advising HPV vaccination to the patients routinely and 48 (22.42%) gynecologists had given HPV vaccination to their daughters. Conclusions: Proper and effective utilization of available facilities would depend on creating better understanding and change in their outlook. Stepping up and strengthening of preventive health care services is essential.